Effects of domestic sewage on characteristics of mangrove communities and their functioning in East Africa - Penha-Lopes, Gil (2010)
Tese de doutoramento, Biologia (Biologia Marinha e Aquacultura), Universidade de Lisboa, Faculdade de Ciências, 2010